Taming SbH3: A Simple and Safe Approach to Using Stibane in Synthesis on a Laboratory Scale - Dollberg, Kevin; Schneider, Selina; von Hänisch, Carsten (Synlett, 2023)
Herein, we present a simple, inexpensive, and readily accessible apparatus for the safe and clean preparation, isolation, and conversion of stibane (SbH3). In this setup, only typical standard glassware and fabric tubes are used. The pure stibane can be obtained in very good yields with very little expenditure of time.
Keywords: antimony; stibane; inorganic chemistry; vacuum synthesis; gas induction